Prognostic value of the optimal measurement location of on-site CT-derived fractional flow reserve. Issue 1 (July 2022) - Nozaki, Yui O.; Fujimoto, Shinichiro; Kawaguchi, Yuko O.; Aoshima, Chihiro; Kamo, Yuki; Sato, Hideyuki; Kudo, Hikaru; Takamura, Kazuhisa; Kudo, Ayako; Takahashi, Daigo; Hiki, Makoto; Dohi, Tomotaka; et al.
Abstract: Background: On-site computed tomography-derived fractional flow reserve (CT-FFR), using fluid structure interaction during multiple optimal diastolic phases, is of incremental diagnostic value. However, few studies have investigated prognosis, with the appropriate measurement location of CT-FFR, as a stand-alone modality. The aim of the present study was to assess the clinical impact on CT-FFR with an appropriate measurement. Methods: A total of 370 consecutive patients (68 ± 10 years, 75% male) who underwent coronary CT angiography (CCTA), showing 50–90% stenosis in at least one major epicardial vessel, were retrospectively analyzed and followed up for a median 2.9 years. CT-FFR values were measured at three points: 1 to 2 cm distal to the target lesion (CT-FFR1cm, 2cm ) and the vessel terminus (CT-FFRlowest ), and a CT-FFR value ≤0.80 was considered to be abnormal. The endpoint was major adverse cardiovascular events (MACE), a composite of cardiac death, non-fatal myocardial infarction, and unplanned revascularization. Results: The incidence of MACE was 6.8% (25/370 patients). The Kaplan-Meier survival analysis in negative CT-FFR1/2cm revealed no significant difference in MACE between negative and positive CT-FFRlowest [ p  = 0.11/0.23 (1/2 cm vs lowest)]. Among 221 patients who did not undergo planned revascularization within 90 days of CCTA, no significant differences were noted in the incidence of MACE between negative and positive CT-FFRlowest ( p  = 0.11). In contrast, the risk of MACE was significantly higher with positive CT-FFR1/2cm [ p  = 0.0198/0.0002 (1/2 cm)]. Conclusions: In terms of the prognosis of patients with moderate to severe stenosis on CCTA, CT-FFR measured 1 to 2 cm distal to the target lesion may be feasible for the safe deferral of unnecessary invasive coronary angiography. Moreover, CT-FFR1/2cm showed better risk stratification than CT-FFRlowest based on future adverse cardiac events. Graphical abstract: Unlabelled Image Highlights: CT-FFR measured 1–2 cm distal to a target stenosis (CT-FFR1-2cm ) was more consistent with decision for revascularization than CT-FFRlowest . CT-FFR1-2cm was a feasible measurement for the safe deferral of invasive coronary angiography. CT-FFR1-2cm showed a good risk stratification on future cardiac events. Any CT-FFR measurement was not a significant marker in critical events.